Menimbang Interpretasi Hadis Rukyat Hilal Yusuf al-Qaradawi - Mufid, Abdul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
Muslims tend to have an adequate understanding of Islam through the Qur’an and Hadith. However, over the years, hadith has been a source of controversy in Islamic law, with the significant problem associated with understanding and determining the beginning of the hijri month. The difference is due to the various perspectives in understanding the observed crescent. This paper aims at discussing the prominent scholar, Yusuf al-Qaradawi in understanding the hadith in question. It argues that the impact of Yusuf al-Qaradawi’s understanding on the ru’yat al-hilal hadith was to unify the performance of fasting and ‘id al-fitr in Europe based on priority, not to unite all Moslems in the world.